2021
DOI: 10.1097/01.aoa.0000796084.31545.b9
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers and the Prediction of Adverse Outcomes in Preeclampsia: A Systematic Review and Meta-Analysis

Abstract: C oronavirus disease 2019 (COVID-19) has a 3.1% fatality rate and is spread primarily through droplets and contact. Anesthetists working in hospitals may perform procedures and provide care involving the respiratory system [eg, cardiopulmonary resuscitation (CPR), airway management, intubation, chest compression, and face mask ventilation], which increases their risk of viral infection and death. To help mitigate these adverse outcomes, the European Resuscitation Council has prioritized staff safety and recomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 0 publications
2
19
1
Order By: Relevance
“…In a meta‐analysis of 33 studies, we recently showed that the sFlt‐1/PlGF ratio may be useful in predicting adverse maternal and perinatal outcomes in women with PE (summary AUC, 0.79 (95% CI, 0.75–0.82)) 12 . In a recent ‘real‐world’ study of 1117 women, the sFlt‐1/PlGF ratio also demonstrated a reasonable performance in predicting adverse maternal and perinatal outcomes (AUC, 0.86), and the addition of the sFlt‐1/PlGF ratio to routinely collected clinical information significantly improved prognostic performance 39 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a meta‐analysis of 33 studies, we recently showed that the sFlt‐1/PlGF ratio may be useful in predicting adverse maternal and perinatal outcomes in women with PE (summary AUC, 0.79 (95% CI, 0.75–0.82)) 12 . In a recent ‘real‐world’ study of 1117 women, the sFlt‐1/PlGF ratio also demonstrated a reasonable performance in predicting adverse maternal and perinatal outcomes (AUC, 0.86), and the addition of the sFlt‐1/PlGF ratio to routinely collected clinical information significantly improved prognostic performance 39 .…”
Section: Discussionmentioning
confidence: 99%
“…They do not recommend the use of these markers to guide management in those with confirmed PE. However, emerging evidence suggests that these biomarkers may have a role in disease prognostication and, therefore, the management of women with confirmed PE 12,39 .…”
Section: Clinical and Research Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preeclampsia has serious consequences for both the mother and fetus, but there is still no effective way to predict and prevent it. Placental growth factor and a soluble fms-like tyrosine kinase 1 (sFlt-1)/placental growth factor (PlGF) ratio have been applied as major biomarkers for prediction of preeclampsia and indicating a poor prognosis for preeclampsia, but clinical usefulness is limited due to differences between several studies [22]. Several previous studies reported that vitamin D deficiency was related to the onset of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…Medicine ® OPEN improve the prediction of early-onset PE, and both this ratio and placental growth factor ratio alone show prognostic promise for adverse outcomes in PE. [10,11] However, the association between adverse pregnancy outcomes and serum levels of isolated antiangiogenic factors and acute-phase proteins remains unknown.…”
Section: Observational Studymentioning
confidence: 99%